Taller Vertical de Historia 02 (2009)
Selección de trabajos de los niveles 1 a 3 del taller.
Keywords: AZPIAZU-SZELAGOWSKI-GONZALEZ; ARQUITECTURA; HISTORIA; ENSEÑANZA; TALLERES; FAU; UNLP; LA PLATA; BUENOS AIRES (PROV); ARGENTINA